Le attività di ricerca del Laboratorio di Archeologia dell'Architettura. Strumenti e metodi. - Fiorini, Andrea (Archeomatica, 2012)
The purpose of this paper is to describe methods of documentation of different archaeological contexts. The first part will show some solutions for the integration of tablet PC within the current standards of archaeological documentation. The second part will describe several techniques of photogrammetric survey for the documentation of burial, wall stratigraphy and structural elements. With the support of photo-modelling and stereophotogrammetry it is possible to record perimeter and surface of each Stratigraphic Unit in three-dimensional space also obtaining isomorphic reproductions of detected object. Moreover the last part will discusses first results of an experiment still in progress: the 3D PDF for publication of the archaeological record.